2020
DOI: 10.1186/s12902-020-00568-7
|View full text |Cite
|
Sign up to set email alerts
|

Changing the patterns of hospitalized diabetic foot ulcer (DFU) over a 5-year period in a multi-disciplinary setting in Thailand

Abstract: Background: After years of decline, the rate of amputations was reported to increase by 50% in the U.S. population between 2009 and 2015. Few studies have examined the most recent trends in hospitalized diabetic foot ulcer (DFU) in Asian patients. This study aimed to examine recent trends and outcomes in hospitalized DFU at a tertiary diabetes center in Bangkok. Methods: We conducted a retrospective study from consecutive hospitalized DFU admissions from 2014 to 2018 at Theptarin Hospital, a multidisciplinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
(42 reference statements)
2
6
0
Order By: Relevance
“…Median LOS was 8-10 days for DFU-related hospital admissions from 2012-17. These results are comparable to a study in Thailand where a median LOS of 8 days for DFU-related hospital admission was reported 28 . In Australia, one study reported an average LOS of 17 days for diabetesrelated foot complications 29 ; however, the sample differed from the current study's specific focus on DFU-related inpatient care.…”
Section: Discussionsupporting
confidence: 85%
“…Median LOS was 8-10 days for DFU-related hospital admissions from 2012-17. These results are comparable to a study in Thailand where a median LOS of 8 days for DFU-related hospital admission was reported 28 . In Australia, one study reported an average LOS of 17 days for diabetesrelated foot complications 29 ; however, the sample differed from the current study's specific focus on DFU-related inpatient care.…”
Section: Discussionsupporting
confidence: 85%
“…Among 103 subjects under study, patients with glucose level below 200mg/dl were found to be high In our study of subject size 103, 56.3% of the patients are previously diagnosed DFU patients and 43.6% are newly diagnosed patients. In our study with subject size of 103 subjects, most number of patients fall under grade-1(30%), grade-2(20.3%), grade-3(20.3%), which states that patients mostly fall in moderate severity, which is similar to a study conducted by Andrew J. Boulton et al in general population of US states that patients who fall under grade-1,2,3 will heal in a moderate time period [6].…”
Section: Resultssupporting
confidence: 78%
“…Higher mortality rates among hospitalized DFU patients were reported to be 10.6% in a Thai study. 36 This study, however, was retrospective and done over a 3-year period, unlike our study which followed patients for only 5 weeks.…”
Section: Dovepressmentioning
confidence: 90%